2007
DOI: 10.1055/s-2007-985740
|View full text |Cite
|
Sign up to set email alerts
|

Acute Compartment Syndrome Related to Stent-Graft Exclusion of a Popliteal Arterial Aneurysm

Abstract: The purpose of this morbidity and mortality case report is to discuss a characteristic of the Viabahn (W.L. Gore, Newark, DE) stent-graft deployment as well as a complication related to wire trauma during endovascular exclusion of a popliteal artery aneurysm. We encountered a phenomenon not described in the literature during deployment of a Viabahn stent graft. This necessitated further wire purchase, which resulted in perforation of a branch vessel within the calf. The rapid recognition of the clinical findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…To avoid this phenomenon, it is necessary to straighten tortuous vessels. Michael et al 8 reported 0.035-inch stiffer wire systems may be favorable. However, a 0.035-inch guidewire is not compatible with a <9 mm-diameter Viabahn stent graft when using 120-cm-delivery catheter length via 7-Fr guiding sheath.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid this phenomenon, it is necessary to straighten tortuous vessels. Michael et al 8 reported 0.035-inch stiffer wire systems may be favorable. However, a 0.035-inch guidewire is not compatible with a <9 mm-diameter Viabahn stent graft when using 120-cm-delivery catheter length via 7-Fr guiding sheath.…”
Section: Discussionmentioning
confidence: 99%
“…However, the present case illustrates more severe bowstring phenomenon. 4 This is a VIABAHN-specific phenomenon which results from its unique structure and deployment mechanism. The SG was covered by a polytetrafluoroethylene (PTFE) jacket, and deployment was accomplished by pulling on a PTFE suture that opens the constraining tetrafluoroethylene jacket from around the device.…”
Section: Discussionmentioning
confidence: 99%